1998
DOI: 10.1016/s0735-1097(98)00309-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after the mustard repair for simple transposition of the great arteries

Abstract: The survival of patients to 28 years with the Mustard repair has been good. Late sudden death is the most worrisome feature. There is a 97% freedom from right ventricular failure to date. The quality of life of late survivors is good, most achieving a normal level of education and employment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
104
1
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(111 citation statements)
references
References 23 publications
1
104
1
5
Order By: Relevance
“…However, even if some authors 19,20 found a progressive decrease of RV function with time, the inevitability of decline of the right ventricle in follow-up remains unproven. Indeed, in some longitudinal studies, 15,16 RV function remained stable during the follow-up period.…”
Section: Right Ventricular Dysfunctionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, even if some authors 19,20 found a progressive decrease of RV function with time, the inevitability of decline of the right ventricle in follow-up remains unproven. Indeed, in some longitudinal studies, 15,16 RV function remained stable during the follow-up period.…”
Section: Right Ventricular Dysfunctionmentioning
confidence: 95%
“…So far, our experience is too limited to draw conclusions. Some authors 9,13,15 have also demonstrated that during exercise stress testing there is a significantly reduced endurance time and a reduced maximal achieved heart rate.…”
Section: Right Ventricular Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Late attrition from RV failure and arrhythmias is an ongoing issue, however, that warrants continued follow-up. 13 The long-term prognosis must be guarded, and in later decades it is possible that many will require cardiac transplantation.…”
Section: Systemic Ventricular Dysfunction and Tricuspid Regurgitationmentioning
confidence: 99%